Party animals, career changers and other pathways into parliament. Issue 1 (2nd January 2018) - Ohmura, Tamaki; Bailer, Stefanie; Meiβner, Peter; Selb, Peter
Abstract : Research on parliamentary careers has paid little attention to variations in pre-parliamentary career patterns and their value in explaining legislators' parliamentary success. Using sequence and cluster analysis, this article identifies typical career tracks taken by Party Animals, Local Heroes, Late Bloomers, Land Legislators, High-Flyers and Career Changers based on a comprehensive dataset of German parliamentarians' biographies (1998–2014). The analysis confirms the role of the party as the primary career facilitator before and within parliament. Nonetheless both Career Changers and High-Flyers climb the greasy pole all the way to the national parliament without much service to the party. The former type, however, suffers from a lack of networks and experience, which is reflected in the limited career success within parliament. This article demonstrates that the use of sequence analysis on career paths offers a promising approach in distinguishing and explaining the opportunities, choices and obstacles MPs face in parliament.